Constitution making in Nepal : report of a conference organized by the Constitution Advisory Support Unit, UNDP, 3-4 March 2007, Kathmandu, Nepal. - UNDP National Conference on "Constitution Making in Nepal" (2007 : Kathmandu, Nepal); United Nations Development Programme (Nepal). Constitution Advisory Support Unit (Kathmandu : UNDP Nepal, 2007)
Report of the UNDP National Conference on "Constitution Making in Nepal", March 3-4, 2007, Kathmandu, Nepal.
Keywords: Constitutional law -- Nepal -- Congresses; Constitutional history -- Nepal -- Congresses; Constitutions -- Nepal -- Congresses